2005
DOI: 10.1007/s10493-005-1019-y
|View full text |Cite
|
Sign up to set email alerts
|

Cannibalism and Interspecific Predation in a Phytoseiid Predator Guild from Cassava Fields in Africa: Evidence from the Laboratory

Abstract: Interspecific predation and cannibalism are common types of interaction in phytoseiid predator guilds, but the extent and nature of these interactions have not been determined yet in phytoseiid guilds composed of African native and neotropical exotic phytoseiid predators found in cassava habitat in southern Africa. We determined in laboratory experiments the level of cannibalism and interspecific predation among the three phytoseiid mite species Euseius fustis, Iphiseius degenerans, and Typhlodromalus aripo in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
2
18
1
Order By: Relevance
“…These data agree with those of Zannou et al (2005) who indicated that the oviposition rate of E. fustis and I. degenerans was significantly lower on conspecific immatures than on limited or abundant provision of M. tanajoa and maize pollens. On the contrary, adult females of N. californicus and P. persimilis cannibalising conspecific larvae were not able to lay eggs compared with those fed on T. urticae (Sabelis 1981;Walzer and Schausberger 1999a;Rahmani et al 2009).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These data agree with those of Zannou et al (2005) who indicated that the oviposition rate of E. fustis and I. degenerans was significantly lower on conspecific immatures than on limited or abundant provision of M. tanajoa and maize pollens. On the contrary, adult females of N. californicus and P. persimilis cannibalising conspecific larvae were not able to lay eggs compared with those fed on T. urticae (Sabelis 1981;Walzer and Schausberger 1999a;Rahmani et al 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Cannibalism rate on conspecific eggs by immatures and adult females of A. exsertus was significantly lower than the predation rate on prey eggs in no-choice tests. These patterns are similar to those reported on adult females of the generalist phytoseiid species, Neoseiulus californicus (McGregor), Euseius fustis (Pritchard & Baker), Iphiseius degenerans (Berlese) and Typhlodromalus aripo DeLeon (Walzer and Schausberger 1999a;Zannou et al 2005). It is interesting to note that the juvenile experience of consuming a given prey is retained through development and affects the predation, oviposition and survival of adult females of phytoseiid predators (Schausberger 2007).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Aggressiveness (chance and latency to attack) and predation rates were moderate in comparison to other phytoseiid species (e.g., Croft et al 1996;Schausberger 1997;Walzer and Schausberger 1999b;Schausberger and Croft 2000;Zannou et al 2005) with shorter latency to attack for P. bickleyi than N. paspalivorus. However, provision of free water in our experiments may have considerably reduced the propensity to IGP (Schausberger 1997).…”
Section: Discussionmentioning
confidence: 78%